Developing participation opportunities for young people with disabilities? Policy enactment and social inclusion in Australian junior sport. Issue 6 (3rd June 2019) - Jeanes, Ruth; Spaaij, Ramón; Magee, Jonathan; Farquharson, Karen; Gorman, Sean; Lusher, Dean
Abstract: Interventions aimed at increasing the participation of young people with disabilities in recreational sport have had mixed success. The authors draw on in-depth interviews with representatives from State Sporting Associations, local government officers and volunteers within community sports clubs in Victoria, Australia, to examine why some sports clubs are unable or unwilling to translate policy ambitions into practice. The findings indicate how by framing disability provision as 'too difficult', 'not core business' and antithetical to competitive success, community sports clubs are able to resist policy ambitions to modify existing structures and develop more inclusive practice. Greater priority needs to be given to transformational inclusion objectives and challenging ableism if clubs are to structurally progress the development of participation opportunities for young people with disabilities.